In Vitro Utilization of Prebiotics by Listeria monocytogenes - Kodešová, Tereza; Mašlejová, Anna; Vlková, Eva; Musilová, Šárka; Horváthová, Kristýna; Šubrtová Salmonová, Hana (Microorganisms, 2024)
Listeria monocytognes is an emerging pathogen responsible for the serious foodborne disease, listeriosis. The commensal gut microbiota is the first line of defense against pathogen internalization. The gut microbiome can be modified by prebiotic substrates, which are frequently added to food products and dietary supplements. Prebiotics should selectively support the growth of beneficial microbes and thus improve host health. Nevertheless, little is known about their effect on the growth of L. monocytogenes. The aim of this study was to evaluate the growth ability of four L. monocytogenes strains, representing the most common serotypes, on prebiotic oligosaccharides (beta-(1,3)-D-glucan, inulin, fructooligosaccharides, galactooligosaccharides, lactulose, raffinose, stachyose and 2'-fucosyllactose and a mixture of human milk oligosaccharides) as a sole carbon source. The results showed that only beta-(1,3)-D-glucan was metabolized by L. monocytogenes. These cell culture data suggest that beta-(1,3)-D-glucan may not be selectively utilized by healthy commensal bacteria, and its role in intestinal pathogen growth warrants further exploration in vivo.
Keywords: Listeria monocytogenes; pathogen growth; beta-(1,3)-D-glucan; prebiotics; oligosaccharides